Adams-Oliver syndrome with unusual central nervous system findings and an extrahepatic portosystemic shunt - Carlos Pérez-García; Yolanda Ruíz Martín; Alejandra Aguado del Hoyo; Carlos Marín Rodríguez; Minia Campos Domínguez (MDPI AG, 2017)
We report a case of a premature neonate girl with scalp and skull defects and brachydactyly of the feet consistent with an Adams-Oliver syndrome (AOS). The patient had central nervous system abnormalities, such as periventricular calcifications, hypoplastic corpus callosum, and bilateral hemispheric corticosubcortical hemorrhagic lesions. A muscular ventricular septal defect and a portosystemic shunt were diagnosed. To our knowledge, this is the first report of congenital supratentorial grey-white matter junction lesions without dural sinus thrombosis in association with AOS. Some of these lesions may be secondary to birth trauma (given the skull defect) whilst others have a watershed location, perhaps as further evidence of vascular disruption and decreased perfusion during critical periods of fetal brain development as the previously proposed pathogenesis of this syndrome.